1980
DOI: 10.3758/bf03199908
|View full text |Cite
|
Sign up to set email alerts
|

Response latency and accuracy in visual word recogniton

Abstract: In a single visual word recognition experiment, the effects of (11 eccentricity of presentation, (2)word length, and (3) word frequency were investigated. The stimuli used were Dutch nouns in two frequency classes of about 15 and 150.10-6 ; word length varied from 1 to 10; eccentricity varied from -4 to +4 deg. The response quality and response latency of 11 subjects were measured. For the correct responses, recognition scores decreased and response latencies increased with eccentricity; both showed asymmetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
33
0

Year Published

1981
1981
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 33 publications
3
33
0
Order By: Relevance
“…Although summation of receptor activity improves the sensitivity to light, and probably to configurational information, it decreases visual acuity and thus hampers the acquisition of visual detail. Some delay in the use of linguistic information from the parafovea is thus expected on purely anatomical grounds (see Schiepers, 1980, for a similar view).It is also possible that acquisition of useful linguistic information from the parafovea requires the prior shifting of attention to it and that this explains why no useful information was extracted from the preview within the beginning 70 ms of a fixation. However, even if acquisition of useful linguistic information from a parafoveal target preview required the allocation of attention to it, it is not clear that such a shift of attention was delayed relative to the onset of a fixation.…”
mentioning
confidence: 93%
“…Although summation of receptor activity improves the sensitivity to light, and probably to configurational information, it decreases visual acuity and thus hampers the acquisition of visual detail. Some delay in the use of linguistic information from the parafovea is thus expected on purely anatomical grounds (see Schiepers, 1980, for a similar view).It is also possible that acquisition of useful linguistic information from the parafovea requires the prior shifting of attention to it and that this explains why no useful information was extracted from the preview within the beginning 70 ms of a fixation. However, even if acquisition of useful linguistic information from a parafoveal target preview required the allocation of attention to it, it is not clear that such a shift of attention was delayed relative to the onset of a fixation.…”
mentioning
confidence: 93%
“…Thus, for example, the probability of correctly identifying a letter embedded in the middle of a trigram drops from 100% in the fovea to approximately 25% at 5 deg (Bouma, 1978). Likewise, the probability of correctly recognizing a word presented in the fovea is virtually 100%, but it drops to about 60% for words presented about 4 deg from ftxation (Bouma, 1973;Schiepers, 1980). Bouma (1973) argued that poorer acuity alone cannot account for the results obtained, and he suggested that visual interference of a masking type, predominantly acting toward the fovea, is responsible for the poorer performance with more eccentrically presented stimuli.…”
mentioning
confidence: 94%
“…In experiments dealing more with perceptual than psychophysical functions, Bouma (1973Bouma ( , 1978 and Schiepers (1980) have demonstrated that the ability to identify a word from a l00-msec exposure or to identify a letter (either in isolation or within a word) decreases as the stimulus is presented farther from ftxation. Thus, for example, the probability of correctly identifying a letter embedded in the middle of a trigram drops from 100% in the fovea to approximately 25% at 5 deg (Bouma, 1978).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A parallel model that does not make this prediction was proposed by Schiepers (1980). Starting from the ®nding that it takes an average 90 msec per degree of eccentricity longer to identify a word (see also Rayner & Morrison, 1981), Schiepers hypothesized that the parafoveal word would be processed in parallel with the foveal word, but with a delay of about 200 msec (because it is typically situated at an eccentricity of 28 ).…”
mentioning
confidence: 99%